(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Parabolic antennas are among the most important devices for long-distance communications because of their significant advantages in terms of directivity, gain, and power handling capabilities. Hat feeds are frequently used as feeders for parabolic antennas because they exhibit low levels of cross-polarisation, low sidelobes, and low reflection coefficients. However, hat feeds possess a limited impedance bandwidth (IBW) range of just 30% and are not suitable for use in wideband applications. More work is being done with the objective of increasing the hat feed’s bandwidth capacity. The fundamental structure of a hat feed comprises a hat sub-reflector, circular waveguide, and dielectric material to provide structural support. The hat feeder had a bandwidth capacity of 10% at first. Later, the Chinese hat feed was introduced and used, resulting in a notable enhancement of the bandwidth, with an increase of 18%. The hat feed’s geometric structure is redesigned with the help of a generic algorithm optimisation to further enhance the bandwidth, resulting in a 33% improvement.